Studies on Some Organic Disulphide Complexes of Metals - Pandey, R.N.; Sharma, R.N.; Sharma, S.R.; Sahay, A.N. (Asian Journal of Chemistry, 2010)
Complexes of some solid and stable di (1-substituted tetrazoline)-5,5´-disulphides have been prepared and investigated using various physicochemical methods such as microanalysis, conductometric, magnetic, infrared, far infrared, UV and visible spectroscopy with Zr(IV), VO(IV), Fe(III), Ru(III), Cr(III), Bi(III), Co(II) and Hg(I) at pH 6. All complexes are generally insoluble in common organic solvent but fairly soluble in DMF. Trans-octahderal configuration for Zr(IV), RU(III) and Cr(III): square planar for Co(II) and Pd(II), polymeric tetrahedral for Hg(I), square pyramidal for VO(IV) and distorted octahedral geometry for Bi(III) having inert pair electrons at one of the corners of the octahedral sites. The crystal field parameter (β) for Cr(III) complex has been calculated and found to be 0.96 which puts these ligands into strong end of nephelauxetic series.